Effect of the hydration temperature on the pore structure of cement paste: Experimental investigation and micromechanical modelling. (September 2018) - Bahafid, Sara; Ghabezloo, Siavash; Faure, Pamela; Duc, Myriam; Sulem, Jean
Abstract: The hydration temperature has a considerable effect on the microstructure of cement paste. The microstructural changes with increasing curing temperature result in a significant decrease of cement mechanical properties. The present work aims at studying these phenomena via micromechanical modelling, based on an experimental characterization of cement microstructure. The pore structure of a class G oil-well cement paste (American Petroleum Institute classification) hydrated at different temperatures, between 7 °C and 90 °C is characterized. Then, the influence of the microstructure variations on the elastic properties of the hardened paste is explored through micromechanical modelling. A previous analysis of the microstructure enabled determining the volume fractions of different phases of a class G cement paste hydrated under different temperatures [1]. A multiscale self-consistent homogenization model is used based on these results to simulate the variations of the mechanical properties with hydration temperature. The results are compared with macro-scale elastic properties obtained from uniaxial compression tests. It is shown that the increasing capillary porosity with elevating hydration temperature, is not sufficient to fully explain this drop of elastic properties. The latter originates mainly from the decrease of the elastic properties of the foam composed of the porous C-S-H intermixed with capillary pores. The pore structure analysis coupled with the micromechanical modelling permitted a back-analysis of the intrinsic porosities of high density and low density C-S-H showing an almost constant LD intrinsic porosity and a significantly decreasing HD intrinsic porosity.